Uit: Karakterschets v. Anna Polak, in: De Hollandsche Revue z.j. (1914). Ned 9/ doos Pol op het IAV?
Uit: Karakterschets v. Anna Polak, in: De Hollandsche Revue z.j. (1914). Ned 9/ doos Pol op het IAV?